Factors Supporting Local Governments in Program Implementation Government and Business Entity Cooperation - Agatha Niken SETYANINGRUM; Nurkholis NURKHOLIS; Made SUDARMA (Indonesia Strategic Sustainability, 2023)
Currently, there is a difference in the need for financing infrastructure development in Indonesia which cannot be provided by the APBN/APBD, nor capital expenditure by SOEs. Therefore, there is a gap between development needs and the availability of funds, causing the emergence of a need for the availability of assistance from outside the government through funding mechanisms outside the APBN to fill this gap. One of the mechanisms currently being promoted by the government is the Public Private Partnership (PPP) program. However, the PPP projects currently underway in Indonesia have yet to run optimally. Several factors are considered to support or hinder the running of a PPP project in a country. In addition, it is also necessary to analyze the form of the PPP project scheme that is most suitable for the conditions in Indonesia.